Software-based performance estimation and real-time thermal analysis of brushless direct current motor with corroded permanent magnets. (October 2018) - Palanivel, Arumugam; Padmanabhan, Sutha
Abstract: The intention of this research is to analyze the thermal behavior and estimate the performance of an inner rotor brushless direct current (BLDC) motor with corroded magnets employed in electric vehicle (EV) applications, using SPEED software. High-speed BLDC motors are widely used for vehicle propulsion, and are mechanically coupled with a transaxle at fixed gear ratios. Such high-speed, low-torque motors are very sensitive to changes in speed and very small change will have a high impact on wheel rotation. However, magnet corrosion has an extremely strong influence on the speed of the motor due to diluted flux density. Here, a detailed analysis of how magnetic corrosion affects the speed, torque and performance of the motor is given. EV motors are employed in open environments and are thus affected by moisture and water. The measurement of performance losses has been studied in detail. The thermal behaviors of the various motor parts are analyzed.